Secure Multiparty computation enabled E-Healthcare system with Homomorphic encryption - Vijaya Kumar, A; Sujith, Mogalapalli Sai; Sai, Kosuri Tarun; Rajesh, Galla; Yashwanth, Devulapalli Jagannadha Sriram (IOP conference series. Materials Science and Engineering, 2020)
With the spread of Covid-19 pandemic it is difficult for many patients to physically visit the Hospitals and get treatment. The Improved technology enable such patients to contact the concern doctors and get diagnosis information online. The security of the sensitive data of the Patients is vulnerable when the information is shared across the network. To address this, we are proposing a novel approach with the Privacy ensured self-care health management schema using Secure Multiparty computation (MPC). Through this approach the patient can share the sensitive data to the Hospital server through the online mode, the data will be shared in the encrypted format which will be matched with the existing data at the Hospital records and the best relevant match based on the smart Index of disease. The privacy preserving is key aspect in this model as the data is shared in the sensitive mode so the Homomorphic Encryption (HE) approach is used to perform computations on the Patient's sensitive data in the encrypted mode and ensure the confidentiality from Intruders to access the information. This model also proposes a novel approach which can overcome many security threats. The patient's data will be shared and used in a more secured manner so the patients specifically the elder who are not advised to visit the public places in this pandemic can also receive better treatment through online.